Community Experiences: Reading and Communication for Civics SB - Terill Lynda (MC Graw Hill, 2005)
The goal of Community Experiences is to help intermediate adult learners, through reading and vocabulary acquisition, understand how and why to participate in their communities while they acquire English. Using this text, students will learn how to utilize community resources-- navigate the local school system, housing market, health care system, library system, etc.